Parrondo's paradox in network communication: a routing strategy - Mishra, Ankit (2024)
The throughput and latency bottleneck in accessing system resources is prevalent in all communication systems. Likewise, communication overhead in modern computer systems is a vital limiting factor in their performance. In this Letter, we propose a routing strategy to improve communication in networks based on Parrondo's paradox. We show that random switching between the shortest-path algorithm and making the local optimum choice (greedy algorithm) yields a significant reduction in total transmission weight compared to when the shortest-path and greedy algorithms are operated separately. This effect recapitulates Parrondo's paradox, where two games/strategies are losing when played alone but create a winning outcome or optimum results when combined in a certain manner. The performance of the switching strategy is further validated under various parameters, and the results indicate that the effect is more remarkable with an increase in the number of packets and the number of nodes in the system. The proposed routing strategy enhances efficiency and scalability in modern computer and communication systems.